Two-way trafficking with Ran - Melchior, Frauke; Gerace, Larry (Trends in cell biology, 1998)
The small Ras-related GTPase Ran is directly involved in nuclear protein import and export. However, the question of how Ran functions in transport is highly controversial. Here, we suggest that Ran is important for the formation, vectorial movement and disassembly of many different classes of transport complexes that traverse the nuclear pore complex during import and export processes. Comparison of Ran with the translation elongation factor Ef-Tu raises the possibility that Ran might also be involved in a proofreading function related to the assembly of import complexes. Although aspects of this model are hypothetical and challenge some current dogma in the field, we believe that it can integrate most of the current data into a coherent picture of the import process.
Gesehen am 17.08.2023